Positional ischaemia of transplant kidney: A rare cause of early graft dysfunction. Issue 5 (18th February 2019) - Li, John Wing; Wong, Germaine; Li, Jennifer; Gruenewald, Simon; Chapman, Jeremy Robert
Abstract: Kinking of the kidney transplant vessels late after the operation is a rare complication that can lead to significant morbidity and mortality. We present a case of positional ischemia of the renal allograft resulting from dynamic and positional kinking of the graft vasculature, which was diagnosed by ultrasonography with the patient standing. The graft was repositioned into the sub‐rectus pocket and the ischaemic injury resolved.